Poor isometric neck extension strength as a risk factor for concussion in male professional Rugby Union players - Farley, T.; Barry, E.; Sylvester, R.; De Medici, A.; Wilson, M. G. (British Journal of Sports Medicine, 2022)
Background: Concussion is one of the highest burden injuries within professional Rugby Union (`rugby`) and comes with a high health and financial cost to players and teams. Limited evidence exists as to the existence of modifiable intrinsic risk factors for concussion, leaving athletes and clinicians with few options when developing prevention strategies. Objective: To investigate whether neck strength is significantly associated with concussion incidence in professional male rugby players. Methods: 225 rugby players were assessed for neck strength at three time points throughout the 2018/2019 season using a method of isometric contraction. Associations with clinically diagnosed concussion injuries are presented as incidence rate ratios (IRRs) with 95% CIs. Results: Thirty concussions occurred in 29 players during the study period; a rate of 13.7 concussions per 1000 hours played. Greater neck strength was observed at mid and end of season time points versus preseason across the study population. There was a significant association between extension strength and concussion; a 10% increase for extension strength was associated with a 13% reduction in concussion rate (adjusted IRR (95% CI) 0.87 (0.78 to 0.98). No other significant associations were observed between concussion incidence and any other unique neck strength range or composite score. Conclusion: Higher neck extension strength is associated with lower concussion rates in male rugby players. Neck strength is a modifiable intrinsic risk factor for concussion and may be an important component of a strength and conditioning regime.